2008
DOI: 10.1097/tp.0b013e318191404c
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Crossmatch Protocol Significantly Increases Access of Highly Sensitized Patients to Deceased Donor Kidney Transplantation

Abstract: Initiation of a virtual crossmatch protocol using solid-phase histocompatibility techniques significantly increased access of sensitized patients to kidney transplantation and was more cost effective. Usage of a virtual crossmatch may facilitate greater sharing of kidneys to improve access to transplantation for sensitized recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 12 publications
(8 reference statements)
0
57
0
4
Order By: Relevance
“…The VXM can be performed prospectively and with at least similar sensitivity to the FC-XM (9,34). In most studies, the correlation of the VXM with the FC-XM was greater than 85% (6,8,35,36). In addition, multiple recent kidney and thoracic transplant studies have reported that a negative VXM was associated with a very low risk for early rejection and good allograft survival even in sensitized recipients (6,9-13).…”
Section: Discussionmentioning
confidence: 99%
“…The VXM can be performed prospectively and with at least similar sensitivity to the FC-XM (9,34). In most studies, the correlation of the VXM with the FC-XM was greater than 85% (6,8,35,36). In addition, multiple recent kidney and thoracic transplant studies have reported that a negative VXM was associated with a very low risk for early rejection and good allograft survival even in sensitized recipients (6,9-13).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of virtual crossmatch ranged from 93% to 100% of flow T-cell crossmatch and 91% to 100% for flow B-cell crossmatch. [6][7][8] The other important advantage of the Luminex platform is introducing a single-antigen identification.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual crossmatching has now become the focal point of organ allocation in the United States and has clearly benefited recipients of deceased and living donor organs (18,27). It is also proving to be especially important for those patients involved in paired exchanges (28).…”
Section: Current and Anticipated Applicationsmentioning
confidence: 99%